Maintenance of stem cell self‐renewal in head and neck cancers requires actions of GSK3β influenced by CD44 and RHAMM. (28th October 2013) - Shigeishi, Hideo; Biddle, Adrian; Gammon, Luke; Emich, Helena; Rodini, Camila O.; Gemenetzidis, Emilios; Fazil, Bilal; Sugiyama, Masaru; Kamata, Nobuyuki; Mackenzie, Ian C.
Abstract: Cells sorted from head and neck cancers on the basis of their high expression of CD44 have high potency for tumor initiation. These cells are also involved in epithelial to mesenchymal transition (EMT) and we have previously reported that cancer stem cells (CSCs) exist as two biologically distinct phenotypes. Both phenotypes are CD44 high but one is also ESA high and maintains epithelial characteristics, the other is ESA low, has mesenchymal characteristics and is migratory. Examining CD44‐regulated signal pathways in these cells we show that CD44, and also RHAMM, act to inhibit phosphorylation of glycogen synthase kinase 3β (GSK3β). We show that inhibitory phosphorylation reduces the formation of both "tumor spheres" and "holoclone" colonies, functional indicators of stemness. GSK3β inhibition also reduces the expression of stem cell markers such as Oct4, Sox2, and Nanog and upregulates expression of the differentiation markers Calgranulin B and Involucrin in the CD44 high /ESA high cell fraction. Transition of CSCs out of EMT and back to the epithelial CSC phenotype is induced by GSK3β knockdown. These results indicate that GSK3β plays a central role in determining and maintaining the phenotypes and behavior of CSCs in vitro and are likely to be involved in controlling the growth and spread of tumors in vivo.